Characterization of biobased epoxy resins to manufacture eco‐composites showing recycling properties. Issue 12 (6th October 2022) - Saitta, Lorena; Prasad, Vishnu; Tosto, Claudio; Murphy, Neal; Ivankovic, Alojz; Cicala, Gianluca; Scarselli, Gennaro
Abstract: The present study details the composite fabrication, characterization, and full recyclability of the biobased polymer resins with flax fiber as the reinforcement. Two different biobased resins are selected by varying the resin hardener combination and curing parameters for the comparison. The optimum parameters for the composite preparation are finalized by evaluating the neat resin's mechanical and glass transition temperature ( T g ) values. According to the results obtained, a biobased epoxy resin cured by a cleavable hardener displayed the highest T g (i.e., 93.5°C) upon a two‐step cure cycle, guaranteeing full recyclability. Subsequently, eco‐composite flat panels are manufactured using the selected formulation reinforced with commercial flax‐based fabric. These panel's flexural strength, modulus, and interlaminar shear strength are measured after each curing step. The recyclability yield of the composite is tested, through a specific chemical process, demonstrating the possibility of separating and recovering both the constituent fibers and resin from the composite panels. Abstract : The article addressed the issue to manufacture, by exploiting natural fibers, recyclable eco‐composites. So, the aim was to find a sustainable disposal route for these materials and to obtain re‐usable recycled products, thus promoting a circular economy approach. This purpose was achieved by exploiting at first a 'design for recycling' path, i.e. by fabricating a recyclable eco‐composite. Secondly, a 'design from recycling' approach was exploited to find a re‐usable strategy for the recycled product obtained.